Corporate Social Responsibility, Religion, and Firm Risk1. (29th April 2017) - Cui, Jinhua; Jo, Hoje; Na, Haejung
Abstract: In this article, we examine the empirical influence of the combined effect of Corporate social responsibility (CSR) and the degree of local community religiosity on firm risk by investigating their unidirectional and endogenous effects. Employing a large US sample, we find an inverse association between CSR–religiosity and firm risk after controlling for various firm characteristics. Also, after mitigating endogeneity bias, we still find a negative association between CSR–local community religiosity and firm risk. We interpret these results to support the social license to operate (SLO) explanation: the lower the level of firm risk, the higher the level of SLO.